Governance Performance of Muslim and Non-Muslim Countries - Devi, Abrista (Management and Sustainability, 2023)
Governance refers to the processes and structures implemented by organizations to ensure that they operate effectively, responsibly, and in accordance with legal and ethical standards. It encompasses the systems and practices by which organizations are directed, controlled, and held accountable. Governance is a critical aspect of various sectors, including business, government, non-profit organizations, and other institutions. This paper studied two groups of Muslim and Non-Muslim countries by comparing their governance performances using several indicators of Worldwide Governance Indicators (WGI) within 2015 to 2019. The objectives are: (1) to evaluate the performance of Muslim world nations compares to the non-Muslim counterparts in terms of governance and related issues; (2) to deduce the implication for policy, in order to improve the performance of economic and governance indicators in countries. In general, the results show that in several indicators, Muslim-based countries have advantages over non-Muslim countries. However, on several other governance indicators, Muslim countries are relatively behind. Therefore, in the future, governance in Muslim-based countries needs to be improved to make it better.